Endoscopic Endonasal and Supraorbital Removal of Tuberculum Sellae Meningiomas: Anatomic Guides and Operative Nuances for Keyhole Approach Selection. Issue 2 (10th June 2021) - Mallari, Regin Jay; Thakur, Jai Deep; Rhee, John H; Eisenberg, Amalia; Krauss, Howard; Griffiths, Chester; Sivakumar, Walavan; Barkhoudarian, Garni; Kelly, Daniel F
Abstract: BACKGROUND: With growing worldwide endoscopy experience, endonasal and supraorbital removal of tuberculum sellae meningiomas (TSM) has increased. OBJECTIVE: To describe anatomic factors for guiding approach selection and outcomes. METHODS: Retrospective analysis of patients undergoing endonasal or supraorbital TSM resection: approach criteria, clinical outcomes, acute magnetic resonance imaging (MRI) fluid-attenuated inversion-recovery (FLAIR)/T2 changes. RESULTS: From 2008 to 2020, 33 patients (mean age 55 ± 11 yr) were identified: 20 (61%) had endonasal and 13 (39%) supraorbital removal. Comparing endonasal and supraorbital approaches, mean tumor volume (3.7 ± 3.5 cm 3 vs 7.7 ± 8.5 cm 3, P  = .07); percent tumor above planum (42% vs 65%, P  = .02), and lateral tumor beyond supraclinoid internal carotid arteries (1.4 ± 2.0 mm vs 4.0 ± 3.2 mm, P  = .006) were greater for supraorbital route. Sellar depth was greater for endonasal route tumors (12.2 ± 2.6 mm vs 9.3 ± 2.4 mm, P  = .003). Endoscopy, used in 10/13(77%) supraorbital cases, was helpful in additional tumor removal in 4/10(40%). Gross total removal and mean volumetric tumor resection were 16/20(80%) and 97.5% by endonasal, and 5/13(39%) and 96% by supraorbital route. Vision improved in 12/17 (71%) endonasal, 6/8 (75%) supraorbital operations, and worsened in 1 (3%) supraorbital case. Endonasal approach with optic canal decompression increased over study period: 15/20 (75%) endonasal patients vs 1/13(8%) supraorbital ( P  < .001). Postoperative FLAIR/T2 MRI changes occurred in 2/12 supraorbital and 0/20 endonasal cases. CONCLUSION: In our experience, both endonasal and supraorbital routes are safe and effective for TSM removal. Greater tumor extension below planum and medial optic canal invasion favor endonasal route, while larger size and lateral extension favor supraorbital route. Given high frequency of TSM growth into optic canals and better access for medial optic canal tumor removal, endonasal route may be preferred for most TSMs. Graphical Abstract: